Cardiac magnetic resonance imaging in unclear cases of ventricular interdependence: a case series. Issue 7 (18th July 2021) - Moseley, Alex; Mazur, Wojciech; Ahmad, Saad
Abstract: Background : Diagnosis of constrictive pericarditis requires demonstration of interventricular interdependence which can prove difficult even with invasive haemodynamics. Its treatment requires invasive surgical procedures prior to which diagnostic certainty is necessary. Cardiac magnetic resonance imaging (MRI) is an underutilized tool for identification of this pathology. Case summary : We present two cases of heart failure due to interventricular interdependence with inconclusive invasive haemodynamic. Prior to recommending invasive surgical treatment, confirmation of the diagnosis was required. This was achieved using cardiac MRI leading to pericardiectomy followed by clinical improvement. Discussion : These cases demonstrate the clinical utility, sensitivity, and specificity of cardiac MRI for ventricular interdependence.